2020
DOI: 10.1002/adpr.202000088
|View full text |Cite
|
Sign up to set email alerts
|

Coherence‐Tailored Multiwavelength High‐Speed Quantitative Phase Imaging with a High Phase Stability via a Frequency Comb

Abstract: Coherent imaging enables noninvasive, label‐free, and quantitative monitoring of the dynamic motions of transparent microobjects requested in life sciences, biochemistry, material sciences, and fluid mechanics. Quantitative phase imaging (QPI), a coherent imaging technique, provides full‐field optical phase information through light interference. The use of coherence, however, inevitably accompanies phase ambiguity and coherent artifacts, such as speckle, diffraction, and parasitic interference, which severely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The QPI setup in our study is shown in Figure 2a [17]. The configuration included a frequency comb (FC-1500-250-WC, M-VIS, Menlo Systems, Planegg, Germany) that was used as a speckle-tailored coherent light source for QPI to study the dynamic of cellular changes such as osmotic swelling [18].…”
Section: Qpi Setupmentioning
confidence: 99%
“…The QPI setup in our study is shown in Figure 2a [17]. The configuration included a frequency comb (FC-1500-250-WC, M-VIS, Menlo Systems, Planegg, Germany) that was used as a speckle-tailored coherent light source for QPI to study the dynamic of cellular changes such as osmotic swelling [18].…”
Section: Qpi Setupmentioning
confidence: 99%
“…[1][2][3][4][5] Due to its high stabilities in the frequency and time domains, the frequency comb has been widely used in various applications, for example, spectroscopy, imaging, communications, and so on. [6][7][8][9][10] Among them, the dual-comb technique is a direct application of the frequency comb and shows prominent advantages in the fast spectroscopy without a need of any moving part. In comparison, traditional infrared and terahertz spectrometers (for instance, the Fouriertransform infrared (FTIR) and the time domain spectrometers) need mechanical scanning mirrors for obtaining a complete spectrum.…”
Section: Introductionmentioning
confidence: 99%